The socio-economic and spatial transformation of Polish cities after 1989 - Jerzy J. Parysek (Dela, 2004)
The aim of this paper is to present the socio-economic and spatial transformation of Polish cities after 1989. The Polish changes reached the structures of the three basic subsystems of the state: political (power), social (society), and economic (the economy). The systemic transformation that has taken place in Poland after 1989 is most readily visible in towns, although it was introduced in the country as a whole. For the development and transforma-tion of towns, the most important were the introduction of local government structures and the market model of the economy. The restitution of local government has ensured towns an authentic manager authorised to perform his function by the local community. The in-troduction of the market model to the economy has resulted in its privatisation and the ap-pearance of enterprise and competition. Towns, especially the biggest cities, have become attractive locations for investment. Cities with a balanced economic structure and well-de-veloped infrastructure had much better chances for growth to start with. Unfortunately, the transformation period has also had some detrimental effects, the most important being un-employment and all kinds of social deviance. However, Polish cities are certainly different today and resemble Western cities to a greater extent than did the so-called socialist towns built along theoretically beautiful but practically ineffectual ideological lines.